Psychiatric morbidity and illness behaviour in female neurological in-patients. Issue 11 (November 1988) - Metcalfe, R; Firth, D; Pollock, S; Creed, F
Abstract : Ninety three female neurological in-patients were assessed in a collaborative neurological and psychiatric study. An overall prevalence of definite psychiatric disorder of 34% was found, depression being the most common diagnosis. Psychiatric morbidity was most common when the neurologist felt that the presentation could not be explained by a neurological disorder. The majority of such patients had symptoms which could be explained by the psychiatric disorder but a substantial number could not be given a definite diagnosis. The General Health Questionnaire was not found to be a useful screening instrument in this setting.